Diagnosis of Clinical Variants of Pityriasis Rosea and PR-like Rashes Produced by Drugs or after COVID-19 Infection/Vaccination - Francisco Urbina; Emilio Sudy (Achievements and Challenges of Medicine and Medical Science Vol. 12, 2025)
Pityriasis rosea (PR) is a common erythemato-squamous dermatosis which almost always, is easily diagnosed. Mostly the disease presents in its classical form. However, clinical dermatology is all about variations and PR is not an exception. Variants of the disease in some cases may be troublesome to diagnose and confuse clinicians. Prompt diagnosis of the condition becomes essential to avoid unnecessary investigations. We hereby review and illustrate the typical and atypical presentations of the disease, including diverse forms of location and morphology of the lesions, the course of the eruption, and its main differential diagnoses. Although histologic features are not specific, they strongly correlate with dermoscopic findings, a new helpful diagnostic tool. Comparisons among the classical form with other variable findings in pediatric age, dark-skinned people, or its presentation during pregnancy are also analysed, so as the multiple causes of PR-like rashes produced by drugs or vaccinations. During the recent COVID-19 pandemic, PR and PR-like eruptions presented either during COVID-19 infection or after COVID-19 vaccinations, with many polymorphic manifestations. Recent findings that suggest a viral reactivation of human herpesvirus 6 and 7 in the origin of PR and its therapeutic alternatives are commented on.